PERLINDUNGAN HUKUM PASAR TRADISIONAL TERHADAP PERKEMBANGAN TOKO MODERN DI KABUPATEN BOGOR - Danu Suryani; Martin Roestamy (JURNAL HUKUM DE'RECHTSSTAAT, 2016)
This study aims to determine the direction, obstacles and the best models in the legal protection of Traditional Markets in Bogor. The local government has implemented several programs such as modernization and markets building systems of Modern Stores also published Regulation No. 11 Year 2012 about structuring and development of Traditional Markets. The program wasn’t appropriate in the view of modernization market bulding  as well as local regulations put Traditional Market in hard position as well as the rent price isn’t affordable  for small traders and it can erode the local wisdom, it seems like suspending the failure of traditional market. The study concluded that the legal protection for both traditional market today is a model of traditional market-based that not only develops Traditional Market physically, but also can protect the local wisdom, values or cultural norms in Traditional Markets and lead Traditional Market as a place for the Farmers and local SMEs to display agricultural products, so that the traditional market can be a venue for sightseeing and socializing as well as supporting the development of Farmers and local SMEs and do not intersect with Modern Store.